2014
DOI: 10.1016/j.ab.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive mass spectrum assay to characterize engineered methionine adenosyltransferases with S-alkyl methionine analogues as substrates

Abstract: Methionine adenosyltransferases (MATs) catalyze the formation of S-adenosyl-L-methionine (SAM) inside living cells. Recently, S-alkyl analogues of SAM have been documented as cofactor surrogates to label novel targets of methyltransferases. However, these chemically synthesized SAM analogues are not suitable for cell-based studies because of their poor membrane permeability. This issue was recently addressed under a cellular setting through a chemoenzymatic strategy to process membrane-permeable S-alkyl analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…(98, 99) Upon the completion of the transfer reaction, PKMTs release the methylated product and a byproduct S -adenosylhomocysteine (SAH) for another catalytic cycle. (19, 100) As detailed below, the structures of many PKMTs have been elegantly tuned to promote the stepwise catalysis.…”
Section: Pkmt-catalyzed Methylation: Cofactor Substrates and Enzyme mentioning
confidence: 99%
See 2 more Smart Citations
“…(98, 99) Upon the completion of the transfer reaction, PKMTs release the methylated product and a byproduct S -adenosylhomocysteine (SAH) for another catalytic cycle. (19, 100) As detailed below, the structures of many PKMTs have been elegantly tuned to promote the stepwise catalysis.…”
Section: Pkmt-catalyzed Methylation: Cofactor Substrates and Enzyme mentioning
confidence: 99%
“…(21, 270) Human MAT2A I117A variant was shown to be the so-far most efficient enzyme to process bulky S -alkyl methionine analogs into the corresponding SAM analogs. (19, 270) With G9a and GLP1 as examples, we showed that ( E )-hex-2-en-5-ynyl homocysteine (Hey-methionine analog) can be processed by the I117A variant of human MAT2A into the corresponding Hey-SAM. (270) In the presence of the BPPP-feasible G9a and GLP1 mutants (Y1154A of G9a and Y1211A of GLP1), histone H3 and other chromatin targets of G9a and GLP1 can be efficiently labeled.…”
Section: Profiling Protein Lysine Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, F. Truong [11] used a chemical procedure to synthesise Sahc and proved its incorporation into a GFP variant upon feeding Met-auxotrophic Escherichia coli cells. In addition to its translational activity, Sahc is also metabolically active, since it serves as a substrate for Met-adenosyltransferases (MATs) which are crucial enzymes in the biosynthesis of the central metabolite S-adenosylmethionine (SAM) [12,13,14,15]. Met is also the standard starting residue in ribosomal translation, although 60% of these residues are removed by N-terminal processing in E. coli [16].…”
Section: Introductionmentioning
confidence: 99%
“…1 (A) Previous work showed that methionine analogues and ATP can be converted by methionine adenosyltransferase (MAT) to AdoMet analogues. [23][24][25][26]30 These were used as cosubstrates in alkylation reactions catalyzed by promiscuous methyltransferases (MTases). (B) In this work, we show that methionine or analogues together with ATP analogues can be converted to nucleoside-modified AdoMet analogues (NM-AdoMets) allowing for selectivity among different MTases.…”
mentioning
confidence: 99%